2020
DOI: 10.3349/ymj.2020.61.9.797
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Sensitization to Inhalant Allergens in Korean Children Over the Last 10 Years

Abstract: Purpose: Climate and lifestyle changes increase an individual's susceptibility to various allergens and also the incidence of allergic diseases. We aimed to examine the changes in sensitization rate for aeroallergens over a 10-year period in Korean children. Materials and Methods: We retrospectively reviewed the medical records of 4493 children who visited the allergy clinic at a tertiary hospital in Korea for allergic rhinitis or asthma from January 2009 to December 2018. The serum specific immunoglobulin E (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(58 reference statements)
1
7
1
Order By: Relevance
“…Increased sensitization to common inhaled allergens was seen in other countries including Germany and Korea, 13,14 which were in agreement with the results of the present study, suggesting a worldwide trend. These changes in sensitization rates may be attributed to the adoption of modern lifestyle, economic development, as well as climate change which increased allergenicity of pollen.…”
Section: Discussionsupporting
confidence: 93%
“…Increased sensitization to common inhaled allergens was seen in other countries including Germany and Korea, 13,14 which were in agreement with the results of the present study, suggesting a worldwide trend. These changes in sensitization rates may be attributed to the adoption of modern lifestyle, economic development, as well as climate change which increased allergenicity of pollen.…”
Section: Discussionsupporting
confidence: 93%
“…The average number of positive allergens has not changed over time although the prevalence of allergic diseases has increased. These findings are different from those of the previous study that reported an increase in the rate of multiple allergen sensitizations in Korean children 31 . As the subjects in this study are adults, they are already exposed and accustomed to the external environment changes and inhaled allergens, resulting in little additional sensitization to the allergens compared to children.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we investigated the clinical characteristics of patients with allergic rhinitis and/or asthma who sensitized against at least one of the common aeroallergens in Guangzhou. Although there are geographical differences, house dust mite sensitization can be said to be characteristic of all atopic populations in Asia [13,14]. The prevalence of HDM sensitization in atopic individuals in some Asian countries have been reported rates of between 60% and 80% [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, signi cant differences in age and family allergy history were observed between AR and AR&AS. The median age (IQR) of the AR patients was 28 (14,35), and 61.29% (57/93) AR patients had a family allergy history while only 33.90% (60/177) in AR&AS patients (P =0.001) (Table 2).…”
Section: Clinical Characteristics and Allergen Positive Rate In Patie...mentioning
confidence: 99%